KETERANGAN AHLI VISUM ET REPERTUM DALAM PEMBUKTIAN PERKARA KEKERASAN DALAM RUMAH TANGGA - Salim, Kartika Agus (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
Based on Article 183 of Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP), it can be concluded that before a judge imposes a crime on a suspect/defendant, the judge needs two pieces of evidence. This evidence serves to strengthen the judge's confidence in the criminal act committed by the suspect/defendant. However, at the conference stage at the Sintang District Court Session, the expert witness who was requested was not present and at the conference the one who read the statement was the Public Prosecutor, so according to the researcher the expert witness was absent but the conference continued and in the end the expert witness' statement was confirmed even though he was not present in person. offline but online. Therefore, the author was interested in conducting a study entitled "Expert's Statement on Visum Et Repertum in Proving Domestic Violence Cases (Case Study of Decision Number 16/Pid. Sus/2023/PN. Stg.   The power of the Visum et Repertum as documentary evidence in revealing a criminal offense that has been imposed. Visum et Repertum is evidence that cannot be used without being supported by other evidence, so Visum et Repertum cannot be said to be evidence that stands alone.  Violence against women, and applied to national laws and regulations, Law Number 23 of 2004 concerning the Elimination of Domestic Violence. These laws and regulations regulate clearly and in detail the forms of violence, criminal sanctions received by perpetrators, the rights of victims of domestic violence and regulate protection for victims of domestic violence, both temporarily and by issuing protection orders from the court.  From the judge's considerations above, the defendant's actions fulfilled the elements contained in article 44 paragraph (1) of Law number 23 of 2004 concerning Domestic Violence.  So the defendant was found guilty of committing the crime of domestic violence. During the trial examination, no justification or excuse was found so that the defendant could be held responsible and could be accused of violating the provisions of the criminal charge.